Non-volatile electric field-mediated magnetic anisotropy in CoZr/ PMN-PT structure - Wang, Zhiling; Zhu, Dengyu; Liu, Fufu; Zhou, Cai; Jiang, Changjun (Frontiers in Materials, 2023)
The electric field-mediated, room-temperature (RT) magnetic anisotropy of CoZr/Pb(Mg1/3Nb2/3)O3–PbTiO3 (PMN–PT) heterostructures, in which the easy axis of the CoZr layer was along either the [01-1] or [100] direction of PMN–PT, was investigated. The two samples were measured with a vibrating sample magnetometer and by ferromagnetic resonance. For the [01-1] easy-axis direction sample, when an electric field was applied, the direction of the easy and hard axes remained in almost the same position. However, for the [100] easy-axis direction sample, the applied electric field changed the directions of the easy and hard magnetization axes, attributable to the competition between magnetic uniaxial anisotropy and piezostrain anisotropy. Nevertheless, the change of the resonance field with the electric field––measured by ferromagnetic resonance––exhibited non-volatile behavior, which possibly indicates magnon-driven magnetoelectric coupling in the CoZr/PMN–PT heterostructure. These results can be applied in microwave filters.